2017
DOI: 10.24051/eee/67281
|View full text |Cite
|
Sign up to set email alerts
|

Heat mitigation by greening the cities, a review study

Abstract: In the past decades, many studies have proposed urban greening as a method to mitigate the rising temperatures in cities and urban heat islands. The cooling effect of urban green spaces can be divided into two components; cooling intensity and cooling extension. These two components are affected by different factors. This paper provides a review of research on the impact of urban greening on temperature and on the parameters that have an effect on that. Based on this review, two categories that have an effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 147 publications
(205 reference statements)
0
10
0
Order By: Relevance
“…Mindful of the limits to human acclimatisation, there is a strong incentive to limit exposure to dangerous heat where possible. Because heat stress is a phenomena that has been, and will continue to be, experienced mainly in cities (Fischer et al, 2012), there is much scope to achieve this through physical modification of urban environments (Ahmadi Venhari et al, 2017; Taleghani, 2017). However, it is critical that studies exploring this prospect do so using heat-humidity indicators in place of air temperature; ‘greening’ cities through the introduction of more vegetation may well reduce the latter, but its influence on the former is unclear (Hass et al, 2016).…”
Section: Synthesis and Future Outlookmentioning
confidence: 99%
“…Mindful of the limits to human acclimatisation, there is a strong incentive to limit exposure to dangerous heat where possible. Because heat stress is a phenomena that has been, and will continue to be, experienced mainly in cities (Fischer et al, 2012), there is much scope to achieve this through physical modification of urban environments (Ahmadi Venhari et al, 2017; Taleghani, 2017). However, it is critical that studies exploring this prospect do so using heat-humidity indicators in place of air temperature; ‘greening’ cities through the introduction of more vegetation may well reduce the latter, but its influence on the former is unclear (Hass et al, 2016).…”
Section: Synthesis and Future Outlookmentioning
confidence: 99%
“…Other studies showed that evolution of microclimatic conditions in such areas is much more unstable than in larger green zones and that they may act as heat islands under specific conditions, but the overall cooling potential is not necessarily much lower than that of larger parks (Cao et al 2010); moreover, small parks might also cool the neighboring streets in some conditions (Chang, Li 2014). Extensive reviews on the effect of small urban green area focused on identifying the relation between cooling potential and most relevant parameters were recently carried out (Venhari et al 2017;Saaroni et al 2018). Well-vegetated courtyard gardens were monitored in Tel Aviv, Israel in 1994(Shashua-Bar, Hoffman 2004.…”
Section: Influence Of Small Urban Green Areasmentioning
confidence: 99%
“…On the other side, evapotranspiration consists in the loss of water to the atmosphere from a plant [9]. Then, there is an energy consumption of the surrounding environment, increasing latent heat and humidity and, consequently, reducing air temperatures [10]. Thanks to these two processes urban green spaces are, in general, cooler than their surroundings and this effect is called Park Cool Island (PCI), also known as Cool Island Effect, that is, the difference between air temperature inside and urban green space and the built area around.…”
Section: Introductionmentioning
confidence: 99%